„[...] to odejść trzeba tak po prostu”. Symbolika śmierci w artystycznych lirykach Bolesława Taborskiego - Budzik, Justyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Artykuł poświęcony jest artystycznym wierszom Bolesława Taborskiego, które potwierdzają, że dorobek liryczny polskiego poety emigracyjnego wyróżnia myślenie czysto wizualne, jak określa to J.J. Wundenburger. Głównym celem szkicu jest ukazanie roli, jaką sztuka malarska i wizualna pełni w twórczości poetyckiej Taborskiego. Autorka skupia się na analizie trzech wierszy, w których poeta podejmuje zagadnienie starości, odchodzenia i umierania. Najważniejszym punktem odniesienia są tu wybrane prace malarskie i wizualne Rembrandta Harmenszoon van Rĳn, Stanleya Spencera i Tadeusza Kantora. Taborski sytuuje symboliczną analizę tych dzieł w kontekście własnej myśli egzystencjalnej i ontologicznej. W ten sposób poszukuje odpowiedzi na pytanie, jak oswoić lęk przed tym, co nieuchronne i nieodgadnione.

The article focuses on the artistic poems of Bolesław Taborski, which prove that the poetic oeuvre of this Polish émigré writer is distinguished by his visual way of thinking, as defined by J.J Wunderburger. The main objective of the manuscript is to present the role which painterly and visual art plays in Taborski’s lyrical works. The author of this article concentrates on the analysis of three poems in which the writer discusses the phenomena of old age and death. In this paper the selected works of Rembrandt Harmenszoon van Rijn, Stanley Spencer and Tadeusz Kantor serve as the most significant points of reference. The symbolic analysis of these artistic pieces is set in the context of Taborski’s existential and ontological reflections. In this way the poet tries to find the answer to the question of how to tame anxiety and fear of inevitable and mysterious phenomena such as death.
“(...) so one should leave just like that”. The Symbolism of Death in the Artistic Poems of Bolesław Taborski
Keywords: myślenie wizualne; starość; śmierć; visual thinking; senility; death